If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x-3)/6=2(x+7)/13
We move all terms to the left:
4(x-3)/6-(2(x+7)/13)=0
We calculate fractions
4x/()+(-(2(x+7)*6)/()=0
We calculate terms in parentheses: +(-(2(x+7)*6)/(), so:We get rid of parentheses
-(2(x+7)*6)/(
We multiply all the terms by the denominator
-(2(x+7)*6)
We calculate terms in parentheses: -(2(x+7)*6), so:We get rid of parentheses
2(x+7)*6
We multiply parentheses
12x+84
Back to the equation:
-(12x+84)
-12x-84
Back to the equation:
+(-12x-84)
4x/()-12x-84=0
We multiply all the terms by the denominator
4x-12x*()-84*()=0
We add all the numbers together, and all the variables
4x-12x*()=0
| 3.4x-1.4x+14=3 | | 13(n)=169 | | 4x+8x-51=85-5x | | 3e+5=25 | | 2c-5c-8=2c-8 | | −2=−1(n−8) | | -2v-16=14-7+9 | | 5x-x²=9 | | 3x+9=9x+23 | | 2.25x=4.25 | | 8x+90=90 | | 3×+4(x-2)=6x-1+8(2x+3) | | -4(-9-2b)=9(-3b+4) | | 41=9v-4 | | -71=1-8v | | 3+9+14z=17z+5 | | 15-3n=5+7n | | 29=v/5-14 | | 3x+4(x-2)=6x-1+8(2x+3) | | -5/x=1/21 | | 10x-9(x+3)=31 | | 10a-28=10a | | -5=4+n | | H(x)=(5-3x)3 | | -48=3(u-7) | | -8+5y=-4y-3y | | -2(v+8)=5v-7+3(3v+3) | | 4x+8(x+8)=-8 | | 6a+7/7=a-1/2 | | 18=-2/5(-12+x) | | 5x+7=-3x-7 | | 2(2x+1)=2x-8x |